(untitled) (Journal of the College of Basic Education, 2022)
The critic opposing the poetics of Muzaffar al-Nawab when claims that objectivity does not exist unless the meaning itself is changed, and this claim came as a response to a possible despair in the face of what he sees ( confusion of interpretations ), also refrring to the current generation of more new interpretations andtheir approaches, and at the same time he sees in Objectivity that is impanted in a radical history is evident in his work and his biography, as a leftist militant from lraq, as he carries a national, national and international thought that is superimposed, integrated or consistent with his human aspirations. Poetic language is not a fixed, dynamic and effective entity, and it is an affiliation before it was descriptive or aesthetic. Ldentity works appeared in the texts of the poet Muzaffar al-Nawab. As a renewed theme that is not restricted, or restless, he is the dreamer at all in a homeland where man is sanctified just as religions are sanctified, because it is the origin and basis of legislation . Poverty, the poor, the hungry, the tormented, and the revolutionaries are the ones to whom the poet belongs and from their concerns he derived his distinctive style biased towards humanitarian and Arab issues wherever I found, his poetry is angry, rebellious, sincere and sincere without disappearing behind any symbol, metaphor, coloration or quackery, and he is the spokesman for the condition of the wounded masses always, transcending himself into a wider global space and comprehensive in a global intellectual position that appeared clearly in his poetic texts .